Psychological-Motivation Model for Improving Technology Education in The Primary Grades - Egamova Ravshanoy Surobjonovna (Scientific Trends, 2025)
This study offered a didactic model for a psychologically informed strategy to help primary school students develop their professional identities, technological literacy, and creative thinking. Students are inspired to learn beyond textbook level by this method. The content of technology education was revised within this framework to consider the interest and developmental requirements of the students. Particularly, emphasis was placed on the development of contemporary skills in autonomous technical thinking, research, and complex problem solving through robotics and drone construction projects. The work combined person-centered, practice-based, and interactive methods to enhance the technological , psychological-didactic, and outcome assessment components of extracurricular activities. With the help of this model, students were able to improve their professional technological competence and direct their own personal growth.
Keywords: Primary education, technological competence, psychological approach, extracurricular activities, creativity, robotics, drone construction, didactic model, problem-solving, project activities.